Can information dissemination reduce last mile payment delays in the public works programme? Evidence from a field experiment in India - Upasak Das; Amartya Paul; Mohit Sharma (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Does information dissemination among beneficiaries of welfare programmes mitigate their implementation failures? We present experimental evidence in the context of a rural public works programme in India, where we assess the impact of an intervention that involves dissemination of publicly available micro-level data on last mile delays in payment and programme uptake, along with a set of intermediate outcomes. The findings point to a substantial reduction in last mile payment delays along with improvements in awareness of basic provisions of the programme and process mechanisms while indicating a limited effect on uptake. However, we find a considerable increase in uptake in the subsequent period, which is potentially indicative of an 'encouragement' effect through the reduction in last mile delays. A comparatively higher impact on payment delay was found for deprived communities. The findings lay a platform for an innovative information campaign that can be used by government and civil society organizations as part of transparency measures to improve efficiency.
Keywords: I30; I38; H75; 330; payment delay; implementation; information; randomization; welfare programme